Educação domiciliar e cultura escolar: as motivações das famílias homeschoolers em rejeitar a escola - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2025)
The objective of this Dissertation is to, after identifying, analyze the main motivations that lead Brazilian homeschooling families to reject School. This is a bibliographical research, with a qualitative, theoretical, epistemological and methodological approach anchored in Dialectical Historical Materialism. It starts from the hypothesis that in its nowadays manifestation, the HS keeps characteristics from old ages, but with specific motivations of the present sociocultural context, crossed by the phenomenon of the ascendancy of the conservative and neoconservative ideological spectrums. As a radiating problem, we asked ―what are the motivations of Brazilian families who practice or defend ED in the 21st century As the main question, we asked ―which were the Brazilian families‘ motivation defenders of HS at 21st century to reject both public and private schools, religious or non-religious?‖ We set as the main objective indentify the main motivations which the families have in mind to reject the school. Our main bibliographical references are: Marx; Engels (2007; 2013; 2016), Marx (1982; 2010), Engels (1984), Frigotto (2000), Gamboa (2003), Eagleton (2000), Apple (2003), Burke (1982), Scruton (2015; 2020), Oakeshott (2020); Santos (2021), Vasconcelos (2005; 2020; 2021) e Ribeiro (2020; 2021). The results show that, in the 19th century, the HS in Brazil had Portugal as a reference and was influenced by the Roman Catholic worldview, and the main motivations were the maintenance of socioeconomic status and the lack of an official education system that met the demands of the time. In its resurgence at the beginning of the century, however, it occurs under influence of the United States of America (USA), and the more religious inspiration is the protestant church. Therefore, even that heterogenous, the HS families are, mainly from medium and high medium class, father and mother presents and conservative christians. Theirs main motivations to reject the school are related to moral (based in the Christianism and/or Creationism); pedagogical (the school has become ―obsolete‖) Social (they‘re afraid of ―bad influences‖); and family (protect the old Christian family, is a mission from God – looking for the ―ideal‖ family). he research did not look at other groups that defend HS. For example, those who, for reasons contrary to the type of pedagogy practiced in school units, prefer unschooling - an informal teaching method that values, in particular, the child's freedom and rhythm.
Keywords: Educação domiciliar; Conservadorismo; Cultura escolar; CNPQ::LINGUISTICA, LETRAS E ARTES